Synthesis and biological evaluation of 2,4,5-trisubstituted thiazoles as antituberculosis agents effective against drug-resistant tuberculosis - Karale, Uttam B.; Krishna, Vagolu Siva; Krishna, E. Vamshi; Choudhari, Amit S.; Shukla, Manjulika; Gaikwad, Vikas R.; Mahizhaveni, B.; Chopra, Sidharth; Misra, Sunil; Sarkar, Dhiman; Sriram, Dharmarajan; Dusthackeer, V. N. Azger; et al. (European Journal of Medicinal Chemistry, 2019)
The dormant and resistant form of Mycobacterium tuberculosis presents a challenge in developing new anti-tubercular drugs. Herein, we report the synthesis and evaluation of trisubstituted thiazoles as antituberculosis agents. The SAR study has identified a requirement of hydrophobic substituent at C2, ester functionality at C4, and various groups with hydrogen bond acceptor character at C5 of thiazole scaffold. This has led to the identification of 13h and 13p as lead compounds. These compounds inhibited the dormant Mycobacterium tuberculosis H37Ra strain and M. tuberculosis H37Rv selectively. Importantly, 13h and 13p were non-toxic to CHO cells. The 13p showed activity against multidrug-resistant tuberculosis isolates. (C) 2019 Elsevier Masson SAS. All rights reserved.

Teixobactin: a paving stone toward a new class of antibiotics? - Gunjal, Vidya B.; Thakare, Ritesh; Chopra, Sidharth; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2020)
Antimicrobial resistance is a serious threat to human health worldwide, prompting research efforts on a massive scale in search of novel antibiotics to fill an urgent need for a remedy. Teixobactin, a macrocyclic depsipeptide natural product, isolated from uncultured bacteria (Elef theria terrae), displayed potent activity against several Gram-positive pathogenic bacteria. The distinct pharmacological profile and interesting structural features of teixobactin with nonstandard amino acid (three Damino acids and L-allo-enduracididine) residues attracted several research groups to work on this target molecule in search of novel antibiotics with new mechanism. Herein, we present a comprehensive and critical perspective on immense possibilities offered by teixobactin in the domain of drug discovery. Efforts made by various research groups since its isolation are discussed, highlighting the molecule's considerable potential with special emphasis on replacement of amino acids. Critical analysis of synthetic efforts, SAR studies, and the way forward are provided hereunder.

Mycobacteria-specific prodrug to overcome phenotypic AMR in mycobacterium tuberculosis - Kumar, T. Anand; Birua, Shalini; Mallojjala, Sharath Chandra; Mukherjee, Piyali; Singh, Samsher; Kaul, Grace; Ramachandran, Aparna; Akhir, Abdul; Chopra, Sidharth; Gadgil, Chetan J.; Hirschi, Jennifer S.; Singh, Amit; et al. (Journal of Medicinal Chemistry, 2025)
Most front-line tuberculosis (TB) drugs are ineffective against hypoxic nonreplicating Mycobacterium tuberculosis (Mtb), largely due to poor permeability, leading to reduced drug accumulation and target engagement. To overcome this phenotypic antimicrobial resistance (AMR), we developed nitroheteroaryl prodrugs for Moxifloxacin (MXF), a front-line TB drug. These prodrugs are activated by bacterial nitroreductases (NTR), which are overexpressed in hypoxic Mtb. NTR-mediated electron transfer and protonation facilitate rapid cleavage of the protective group, releasing active MXF. The lead prodrug exhibited comparable efficacy to MXF in replicating Mtb and significantly enhanced lethality in nonreplicating Mtb. Drug accumulation studies confirmed a modest but significant increase in MXF levels in nonreplicating Mtb treated with the prodrug, suggesting improved permeability. A mathematical model integrating growth and drug-killing kinetics further elucidated how permeability differences impact lethality. Together, these findings highlight enzyme-activated prodrugs as a promising strategy to address phenotypic AMR in Mtb